Direct evidence for nest predation by the edible dormouse (Glis glis, Rodentia) in open-cup nesting songbirds - Adamík, Peter; Weidinger, Karel (Journal of Vertebrate Biology, 2024)
For most rodent species, there is a lack of detailed studies of their diet to understand their predatory impact on other vertebrate taxa. For this reason, rodent predation on bird nests remains a largely unexplored field. Here we provide the first direct evidence, with the use of time-lapse video surveillance, that edible dormouse Glis glis depredated or attempted to depredate eggs and nestlings of two open-nesting passerine species, the Eurasian blackcap Sylvia atricapilla, and the common blackbird Turdus merula in a central European woodland. In the blackcap, we detected three predation events. In the first two cases, edible dormouse drove away incubating/brooding females and preyed upon either the eggs or the nestlings. The third case documents egg predation on an abandoned nest. In the blackbird, we document a single case of dormouse attacking a brooding female. The female and nestlings managed to escape. The fifth case documents an attempt to forage on eggs in an abandoned song thrush Turdus philomelos nest. Our observations provide evidence for dormice predation on passerine birds and highlight the value of direct nest surveillance for documenting rodent predation on birds.